Assessment of Socio-Demographic Characteristics and Risky Behaviours among Sex Workers in Rivers State - Opirite , Peter-Kio (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2017)
Sex work in Nigeria is illegal and Female sex workers are among HIV/AIDS most at risk groups. This study assessed socio-demographic characteristics and risky behaviours among sex workers in Rivers State. A descriptive cross sectional design was used. A cluster sampling technique was used and the entire available sample who agreed to participate in the study was sampled using interviewer administered questionnaire. Data collected was analyzed using descriptive statistics. More(40.2%) of the respondents are aged 20-24years with a mean age of 24.7±4.6years, 62.5% had secondary education, 19.2% higher education, 85.6% single. Majority (89.9%) consumed alcohol of which 36.9% are occasional drinkers, 36.6% daily drinkers. More (65.9%) had non-paying boyfriends and 36.6% of those with non-paying boyfriends use condom with their partners. More than a quarter (37.2%) had non-paying casual friends of which 70.5% used condom with their casual non-paying friends. Majority (85.1%) of sex workers used condom with their paying sexual partners. Sex workers engaged in risky behaviours that can predisposed them to STIs including HIV/AIDS. There is the need for intervention to deal with demographic variables and consistent supply of condom and condom use.